Loose anagen hair syndrome, type b. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2022)
Loose anagen syndrome (LAS), is a condition in which the hair has little resistance to traction and can be easily plucked out without pain, due to a faulty anchoring of the hair to the sheaths of the hair follicle. Preschool age and female sex are most affected. However, it is possible that these data are influenced by the progressive spontaneous improvement with time regarding the age and by the greater evidence in female sex due to the greater tendency to wear long hair that makes the problem more visible. The belief that people with fair hair are mainly affected has been unfounded (1). The syndrome is often inherited with an autosomal dominant trait and in some cases mutations have been demonstrated in the K6HF and K6IRS genes that code for keratins expressed in the hair sheaths (3, 6). These mutations would be responsible for premature keratinization of the hair sheaths and therefore for their lower adhesion to the cuticle of the hair shaft and easier fall. LAS can also be associated with various hereditary diseases, more frequently with Noonan syndrome (4). However, there are also sporadic cases of LAS. (...).